Evalation of Sociodemographic Characteristics of Adolescent Admitted to Pediatric Emergency Department Due to Suicide Attempts - Bekir Yigit Develi,Hüseyin Dag*,Emre Aygün,Ahmet Dogan,Emine Türkkan,Nevin Çetin Dag,Seda Erbilgin,Ömer Faruk Beser (Innovative Journal of Medical and Health Sciences, 2019)
Background and Aim: In adolescence, suicide is accepted as an increasing problem in our country as in the whole world. It is important to make definitions about suicide attempt, to identify risk factors, and to recognize high-risk adolescents. The aim of this study was to investigate the sociodemographic characteristics of children admitted to the pediatric emergency department because of suicide attempt retrospectively. Material and Method:The records of 102 children admitted to the Pediatric Emergency Department of the Health Sciences University Okmeydan? Training and Research Hospital for suicide attempt, aged between 12-18 years were retrospectively analyzed. Results: The age distribution of the children included in the study was 11-16 years and the mean age was 13.83 ± 1.42 years. Among patients 73.5% (n = 75) were female and 26.5% (n = 27) were male. Overdose drug intake was the most common method in suicide attempts (85.3%). Analgesic-anti-inflammatory drugs were the most commonly used drugs with a rate of 52.9% (n = 46). Psychiatric problems were detected in 71% of the patients who were followed up by psychiatrists. Conflict with family and girlfriend / boyfriend were the most common triggering factors for suicide attempt. Conclusion: Regarding our results, being female and having mental disorders and problems in social relations were determined as important factors related to suicide attempt in adolescents. Key words: Adolescent, suicide, psychiatric disorders, socio-demographic features